Efficient photocatalytic degradation of antibiotics by visible light-driven red phosphorus/ZnAl-LDH heterostructures: Mineralization activity and actual farming wastewater treatment. (25th June 2023) - Zheng, Jiangfu; Fan, Changzheng; Li, Xiaoming; Yang, Qi; Wang, Dongbo; Duan, Abing; Pan, Shuaijun; Zhang, Baowei; Ding, Jinglin; Liu, Junwu
Abstract: A stable, efficient and pollution-free treatment system should be urgently developed to boost the application of green and sustainable photocatalytic materials in practical wastewater composite remediation. two-dimensional (2D) red phosphorus (RP)/ZnAl-LDH (Layered Double Hyroxides) photocatalyst photocatalysts were developed in this study. The optimized RPLDH0.8 (RP/ZnAl-LDH0.8)/Vis system was found with a high tetracycline hydrochloride (TC) degradation rate of 89% in 90 min. Moreover, the total organic carbon (TOC) removal rate was obtained as 21%. As indicated by the results of the experiments and characterization, the fast catalytic process arose from the S-scheme charge transfer pathway in RP/ZnAl-LDH. Furthermore, the liquid chromatography-mass spectrometry (LC-MS) and the radical capture assays were performed to investigate the probable TC photodegradation pathway and the primary reactive radicals in the photocatalytic process. The results of the bio-acute toxicity-based assays suggested that the RPLDH0.8/Vis system detoxified the transformation products. Lastly, the above RPLDH0.8/Vis system was found with high removal rates for other organic pollutants while showing high removal performance in different natural water bodies. Besides, the leaching concentration of total Zn in each of the five cycles of the degradation experiments was significantly lower than the national level discharge standard, suggesting that the RPLDH0.8/Vis system degraded TC without secondary heavy metal contamination. As revealed by the above findings, a novel strategy was proposed to prepare RP/ZnAl-LDH photocatalysts for the photocatalytic degradation of antibiotics. Graphical abstract: Image 1 Highlights: Red phosphorus/zinc-aluminium layered double hydroxide with high activity. Electron transfer can be effectively facilitated by S-scheme heterojunctions. The designed catalytic system is effective in mineralising the actual effluent. Degradation pathway of TC was proposed and its toxicity was evaluated.